A lack of evolution in the very bright end of the galaxy luminosity function from z ≃ 8 to 10. Issue 2 (3rd February 2020) - Bowler, R A A; Jarvis, M J; Dunlop, J S; McLure, R J; McLeod, D J; Adams, N J; Milvang-Jensen, B; McCracken, H J
ABSTRACT: We utilize deep near-infrared survey data from the UltraVISTA fourth data release (DR4) and the VIDEO survey, in combination with overlapping optical and Spitzer data, to search for bright star-forming galaxies at z ≳ 7.5. Using a full photometric redshift fitting analysis applied to the ∼6 deg^2 of imaging searched, we find 27 Lyman break galaxies (LBGs), including 20 new sources, with best-fitting photometric redshifts in the range 7.4 < z < 9.1. From this sample, we derive the rest-frame UV luminosity function at z = 8 and z = 9 out to extremely bright UV magnitudes ( M UV ≃ −23) for the first time. We find an excess in the number density of bright galaxies in comparison to the typically assumed Schechter functional form derived from fainter samples. Combined with previous studies at lower redshift, our results show that there is little evolution in the number density of very bright ( M UV ∼ −23) LBGs between z ≃ 5 and z ≃ 9. The tentative detection of an LBG with best-fitting photometric redshift of z = 10.9 ± 1.0 in our data is consistent with the derived evolution. We show that a double power-law fit with a brightening characteristic magnitude (Δ M */Δ z ≃ −0.5) and a steadily steepening bright-end slope (Δβ/Δ z ≃ −0.5) provides a good description of the z > 5 data over a wide range in absolute UV magnitude (−23 < M UV < −17). We postulate that the observed evolution can be explained by a lack of mass quenching at very high redshifts in combination with increasing dust obscuration within the first 1 Gyr of galaxy evolution.